Weight Reduction After Severe Brain Injury: A Challenge During the Rehabilitation Course. Issue 2 (April 2015) - Aadal, Lena; Mortensen, Jesper; Nielsen, Jørgen Feldbæk
Abstract : Abstract: Background: There is a paucity of studies, which have described malnutrition in patients with acquired brain injury (ABI) across etiology. This study describes weight change, malnutrition, and potential associations in patients with ABI at a subacute inpatient rehabilitation hospital.Method: This is a descriptive cohort study. Ninety-eight patients were admitted in a 3-month period, of whom n = 76 met inclusion criteria. The Malnutrition Universal Screening Tool was used for categorizing patients according to risk of malnutrition.Results: Patients had experienced weight loss of 5.59% ± 5.89% ( p < .001) at admission at the rehabilitation hospital, and patients with traumatic brain injury had experienced a greater weight loss than patients with stroke ( p < .01). Thirty percent of patients were at high risk for malnutrition, and 52% of these patients received enteral or parenteral nutrition at admission at the rehabilitation hospital. No association was found between risk of malnutrition and severity of injury, complications, functional outcome, or length of stay.Conclusion: Results underline the importance that nurses, especially in acute care, adhere to clinical guidelines to minimize weight loss. Special attention should be on patients with traumatic brain injury. Weight gain in the following course of rehabilitation may facilitate positive rehabilitation outcomes.